1990
DOI: 10.1016/0014-5793(90)80946-g
|View full text |Cite
|
Sign up to set email alerts
|

Modelling heme d1

Abstract: The heme d, macrocycle of Ps. aeruginosa dissimilatory nitrite reductase is an iron porphyrin-3,8-dione with a 17-acrylate substituent. We have compared the RR properties of Cu-d,, the copper(I1) TME of extracted heme d,, with those of models that differ only with respect to the acrylate: Cu-17-acrylate-mesoporphyrin-3,8-dione (2) and Cu-mesoporphyrin-3.8-dione (3). The RR spectrum of Cu-d, is very similar to that of 2, including v(C = 0) at _ 1720 cm-I. Replacement of the acrylate with propionate changes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We previously suggested that the v(C=0) modes of the two oxo groups of Cu-dx were accidentally degenerate. 25 For dione models 2-5, 7, and 8, neither the FTIR spectra nor the RR spectra display separate voxo(C=0) modes. The v0X0(C=O) modes of 2-5,7, and 8 need not necessarily be accidentally degenerate to display the observed lack of splitting.…”
Section: Resultsmentioning
confidence: 98%
“…We previously suggested that the v(C=0) modes of the two oxo groups of Cu-dx were accidentally degenerate. 25 For dione models 2-5, 7, and 8, neither the FTIR spectra nor the RR spectra display separate voxo(C=0) modes. The v0X0(C=O) modes of 2-5,7, and 8 need not necessarily be accidentally degenerate to display the observed lack of splitting.…”
Section: Resultsmentioning
confidence: 98%
“…(5,6) electronic, (1,5,6,7) and vibrational spectroscopic (5,8) properties of this class of compounds.…”
mentioning
confidence: 89%